PENGARUH CELEBRITY ENDORSEMENT VS. INFLUENCER ENDORSEMENT VS. ONLINE CUSTOMER REVIEW TERHADAP PURCHASE INTENTION PADA PRODUK SKINCARE - Josephine Jesslyne Helbert; I Gde Surya Putra Ariawan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Social media which initially only functioned as a medium to expand friendships and share one's daily activities, is now starting to turn into a platform used by many companies to share information and carry out marketing activities. One of the marketing strategies carried out by the company through social media is to use the services of an endorser to promote its products through the endorser's personal social media account. There are three types of endorsers studied in this study, namely celebrity endorsers, influencer endorsers, and online customer reviewers, each of which has its own advantages. Therefore, the purpose of this study is to analyze the difference or comparison of the influence of the credibility of the three types of endorsers above on consumer buying interest in the same product. The products used in this study are skincare products. This research was conducted using purposive sampling method by distributing questionnaires to 100 respondents for each type of questionnaire based on different types of endorsers so that a total of 300 respondents were obtained. The collected data was then processed using PLS-SEM as a whole and PLS-MGA to test the effect of moderation. The results obtained in this study are that an influencer endorser has the highest moderating effect among other types of endorsers on the relationship between endorser's credibility towards attitude toward the ad and attitude toward the brand. Meanwhile, the differences between these three types of endorsers do not have a moderating effect on the relationship between endorser's credibility, attitude toward the ad, and attitude toward the brand towards purchase intention.